Analisis Kritis atas Peran Instagram dalam Representasi Pariwisata dan Konstruksi Identitas Budaya: : Studi Kasus Pada Makam Raja Yogyakarta - Kharismawati, Mery; Hidayat, Arief (PT. Data Jaringan Visual Indonesia (Djava), 2025)
Instagram has become a major tool in shaping tourism representation and constructing cultural identity. This research analyzes how the Tomb of the Mataram Kings in Yogyakarta is represented on Instagram @kratonjogja and its impact on tourists' interpretations. Using a critical phenomenology approach, the study argues that Instagram is not merely a promotional platform but also an instrument of symbolic domination that aestheticizes and commodifies cultural heritage. Through digital content analysis, in-depth interviews, and participatory observation, this study reveals that tourists' experiences are increasingly mediated by digital expectations, diluting the historical and spiritual significance of the sites. Consequently, this study underscores the necessity for a critically informed tourism management strategy to mitigate the symbolic dominance of digital platforms while safeguarding the historical-spiritual integrity of cultural sites within contemporary tourism promotion dynamics.